Study on the kinetics of beer continuous fermentation by the yeast cells immobilized in the carriers of ceramics - CHENG Jiang-feng; HE Guo-qing; REN Kai-yang; YU Yong-fei (浙江大学学报. 农业与生命科学版)
The yeast cells immobilized in the rashig ring ceramics carriers were used to beer continuous fermentation. The fermentation kinetics of the growth of yeast, the consumption of substrate and the production of ethanol were studied. The relevant kinetic models were constructed and the best fit parameters were analyzed. When the volume of the reactor is 84.8 L and the flux of wort was more than 6.2 L/h, the effect was preferable.